Transportation Modes During Pandemic Covid-19 in Indonesia - Siti Maemunah; Marta Anggoro (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
The purpose of this study is the selection of transportation modes during the pandemic in Indonesia. This study uses an analysis of the SEM (Structural Equation Model) analysis technique, with a Partial Least Square (PLS) approach. The results of the analysis show that the cost and safety variables do not significantly affect the choice of transportation mode, this is due to the Covid-19 pandemic which resulted in changes in variables community priorities in the selection of transportation modes. While the variables of comfort and compliance with health protocols have a significant effect on the choice of transportation modes which have an impact on reducing the risk of being exposed to COVID-19. Therefore, it is necessary to study the improvement of minimum service standards in order to increase the convenience of users of transportation services and carry out supervision to ensure the implementation of minimum service standards in order to improve comfort and compliance with health protocols.